(The Effect of Temperature and Duration of Freezing Process on The Isolation of Anethole From Star Anise (Illicium verum) - Moestafa, Achmad; -, Chairul; Arifin, Agus (Warta Industri Hasil Pertanian, 1997)
Â Anethol that is used in flavor, fragrance and medicine is the main component of anise oil. Pure antehol has melting point around 21.6 to 22 derajat celcius that is close to room temperature. An attempt to isolate anethole from Star anise oil (Illicum verum) a studied through freezing process has been done. It was found when the oil was cooled to 12 derajat celcius almost all the oil was solidified. The crystal contains 89% anethole that is not pore enough. When the oil was cooled at 14 derajat and 16 derajat celcius, 30% and 7% of the oil was crystallized respectively and contained 90% and 94% anethole. The experiment showed the lower the temperature, the least pure anethole was collected. A technique to isolate anethole from star anise oil can be done by fractional crystallization.Â